Novel Findings into AIRE Genetics and Functioning: Clinical Implications - De Martino, Lucia; Capalbo, Donatella; Improda, Nicola; Lorello, Paola; Ungaro, Carla; Di Mase, Raffaella; Cirillo, Emilia; Pignata, Claudio; Salerno, Mariacarolina (Frontiers in Pediatrics, 2016)
Autoimmune Polyendocrinopathy Candidiasis Ectodermal Dystrophy (APECED), formerly known as Autoimmune Polyendocrine Syndrome type 1 (APS-1), is a paradigm of a monogenic autoimmune disease caused by mutations of a gene, named autoimmune regulator (AIRE). AIRE acts as a transcription factor that promotes immunological central tolerance by inducing the ectopic thymic expression of many tissue-specific antigens. Although the syndrome is a monogenic disease, it is characterized by a wide variability of the clinical expression with no significant correlation between genotype and phenotype. Indeed, many aspects regarding the exact role of AIRE and APECED pathogenesis still remain unraveled. In the last decades, several studies in APECED and in its mouse experimental counterpart have revealed new insights on how immune system learns self-tolerance. Moreover, novel interesting findings have extended our understanding of AIRE’s function and regulation thus improving our knowledge on the pathogenesis of APECED. In this review, we will summarize recent novelties on molecular mechanisms underlying the development of APECED and their clinical implications.